Model polityki zagranicznej Polski w XXI wieku w myśli politycznej głównych orientacji ideologiczno-programowych (Politeja, 2023)
THE MODEL OF POLAND’S FOREIGN POLICY IN THE 21ST CENTURY IN THE POLITICAL THOUGHT OF MAIN IDEOLOGICAL AND PROGRAMMATIC ORIENTATIONSThe aim of the article was to show various ways of creating a model of Polish foreign policy in contemporary political thought situated in the context of the Polish raison d’état in the 21st century. The subjects of the research were the main ideological and political orientations: conservative, liberal, agrarian, social democratic, and nationalist with its derivatives, which had their external emanations in the form of political parties: Law and Justice, Civic Platform, Polish People’s Party, Democratic Left Alliance and New Left, as well as the League of Polish Families and the National Movement including related groups belonging to the ideological family. The structure of the article includes references to the model of foreign policy, taking into account: 1) the characteristics of specific currents of political thought, 2) the prospects of competition for power within the state; 3) shaping the course of Poland’s policy in external relations.